Lack of Epstein–Barr virus infection in Chinese myasthenia gravis patients. (14th May 2013) - Jing, F.; Wei, D.; Wang, D.; Li, N.; Cui, F.; Yang, F.; Chen, Z.; Huang, X.
<x xml:space="preserve">Abstract</x> Objective There are three recent contradictory reports on the incidence of Epstein–Barr virus in the pathogenesis of myasthenia gravis, with all studies carried out in Caucasian patients. The current study evaluated whether Epstein–Barr virus infection had a role in the pathogenesis of myasthenia gravis in a cohort of 30 Chinese patients. Materials and methods Serial paraffin sections of thymic hyperplasia obtained from myasthenia gravis patients were analyzed for the presence of Epstein–Barr virus‐encoded small RNA ‐1 and Epstein–Barr virus latent membrane protein 1 by in situ hybridization and immunohistochemistry, respectively. Epstein–Barr virus+ cervical lymph nodes from lymphoma patients and Epstein–Barr virus‐ thymus specimens obtained during cardiac surgery served as the positive and negative control groups, respectively. Results All the 30 myasthenia gravis specimens were negative for both Epstein–Barr virus‐encoded small RNA ‐1 and Epstein–Barr virus latent membrane protein 1 tests. However, we obtained well‐characterized membrane and cytoplasmic immunohistochemical and in situ hybridization staining for both Epstein–Barr virus latent membrane protein 1 and Epstein–Barr virus‐encoded small RNA ‐1, respectively, in the positive control samples. Conclusions Our results therefore do not support a role of thymic Epstein–Barr virus infection in myasthenia gravis pathogenesis and calls for an integration of methodological and interpretation issues in detecting Epstein–Barr virus incidence in myasthenia gravis patients.